Reptile surveys reveal high species richness in areas recovering from mining activity in the Brazilian Cerrado - Oda, Fabricio H.; Avila, Robson W.; Drummond, Leandro de O.; Santos, Danusy L.; Gambale, Priscilla G.; Guerra, Vinicius; Vieira, Raiaa Romenia S.; Vasconcelos, Tiago S. [UNESP]; Bastos, Rogerio P.; Nomura, Fausto (Walter De Gruyter Gmbh, 2017)
Our study determines the reptile species richness, composition, and habitat use in three areas recovering from mining activity in addition to the adjacent pristine and anthropized areas of a priority region for biodiversity conservation of the Brazilian Cerrado. We also compared our data with published surveys on the Cerrado domain in order to identify areas with unique species composition and/or areas where the reptile composition is more homogeneous. The survey was conducted in the municipality of Niquelandia, northern Goias state, central Brazil, and involved reptile samplings from different physiognomies and water bodies. We found 47 species, including one crocodilian, one chelonian, two amphisbaenians, 17 lizards, and 26 snakes. The list includes 37 species with large geographic distribution, occurring in other morphoclimatic domains, as well as 10 species which are endemic to the Cerrado. Some species recorded for the region are listed in the Appendices I and II of the CITES. Many reptile species were frequently associated with anthropogenic habitats, while others seem to depend on remnants of pristine habitats. Low similarity was found among the 32 sites considered across the Cerrado domain. Ten sites located in Cerrado regions in contact with the adjacent domains have unique reptile composition, whereas most sites largely located in the central area of the domain have reptile communities which are more homogeneous among them. It is important to conduct long-term studies to have patterns of reptile species composition recognized as well as population decline and/or local extinctions and effective reptile conservation actions, with focus on these sites considering their unique species.
Keywords: amphisbaenians; biodiversity conservation; chelonian; crocodilian; lizards; reptile communities; snakes